Immediate Weight Bearing as Tolerated Is Safe Following Intramedullary Fixation of Extra-articular Metaphyseal Proximal Tibia Fractures (OTA/AO 41-A). Issue 1 (January 2023) - Telgheder, Zachary L.; Hill, Brenton; Huang, Kevin; Watson, David T.; Maxson, Benjamin; Infante, Anthony; Donohue, David; Shah, Anjan; Downes, Katheryne; Sanders, Roy W.; Mir, Hassan R.
Abstract : Objectives: To determine whether immediate weight bearing after intramedullary fixation of extra-articular proximal tibia fractures (OTA/AO 41A) results in change of alignment before union. Design: Retrospective Review. Setting: Level I and Level II Trauma Center. Patients/Participants: Thirty-seven patients with 37 proximal tibial fractures, all whom could bear weight as tolerated postoperatively. Eighteen fractures were OTA/AO 41-A2, and 19 were OTA/AO 41-A3. Intervention: Intramedullary nailing of extra-articular proximal tibia fractures. Main Outcome Measurements: Change in fracture alignment or loss of reduction. Results: The average change in coronal alignment at the final follow-up was 1.22 ± 1.28 degrees of valgus and 1.03 ± 1.05 degrees of extension in the sagittal plane. Twenty-five patients demonstrated excellent initial alignment, 10 patients demonstrated acceptable initial alignment, and 2 patients demonstrated poor initial alignment. Five patients demonstrated a change in alignment from excellent to acceptable at the final follow-up. No patient went from excellent or acceptable initial alignment to poor final alignment. Five patients required unplanned secondary surgical procedures. Two patients required return to the operating room for soft-tissue coverage procedures, 2 patients required surgical debridement of a postoperative infection, and 1 patient underwent debridement and exchange nailing of an infected nonunion. No patient underwent revision for implant failure or loss of reduction. Conclusion: Immediate weight bearing after intramedullary fixation of extra-articular proximal tibia fractures (OTA/AO 41A) led to minimal change in alignment at final postoperative radiographs. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.